2011
DOI: 10.1111/j.1438-8677.2011.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of arginase in Arabidopsis thaliana influences defence responses against Botrytis cinerea

Abstract: Arabidopsis possesses two arginase-encoding genes, ARGAH1 and ARGAH2, catalysing the catabolism of arginine into ornithine and urea. Arginine and ornithine are both precursors for polyamine biosynthetic pathways. We observed an accumulation of ARGAH2 mRNA in Arabidopsis upon inoculation with the necrotrophic pathogen Botrytis cinerea. Transgenic lines displaying either overexpression of ARGAH2 or simultaneous silencing of both Arabidopsis arginase-encoding genes were created and their resistance to B. cinerea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 40 publications
7
60
0
Order By: Relevance
“…17 Some stress factors might share the activation of stress responsive pathway in the plant, characterized by arginine concentration per g fresh weight (FW), AtARGAHs knockout and overexpressing lines showed significantly less relative arginine (% of total free amino acids) than that of wild type. 5 All these results were consistent with what Flores et al (2008) and Brauc et al (2012) reported. 2,3 It is reasonable that all AtARGAHs overexpressing lines showed decreased relative arginine, indicating a direct effect of AtARGAHs on arginine pools.…”
Section: Involvement Of Arabidopsis Arginase In Response To Abiotic Ssupporting
confidence: 90%
See 4 more Smart Citations
“…17 Some stress factors might share the activation of stress responsive pathway in the plant, characterized by arginine concentration per g fresh weight (FW), AtARGAHs knockout and overexpressing lines showed significantly less relative arginine (% of total free amino acids) than that of wild type. 5 All these results were consistent with what Flores et al (2008) and Brauc et al (2012) reported. 2,3 It is reasonable that all AtARGAHs overexpressing lines showed decreased relative arginine, indicating a direct effect of AtARGAHs on arginine pools.…”
Section: Involvement Of Arabidopsis Arginase In Response To Abiotic Ssupporting
confidence: 90%
“…1,4,17 As shown in Figure 1, manipulating the expression of AtARGAHs supplied a good version to investigate the link between NO and polyamines, especially in plant responses to abiotic stress. [2][3][4][5] Our previous research together with other published data confirmed that proper levels of NO might be necessary and beneficial for plants in response to both abiotic stress and disease resistance. [6][7][8][9][10][11]13,14 As to polyamines, overexpression of several polyamine metabolism genes including ADC and SPMS resulted in increased polyamines and enhanced abiotic stress tolerance, while knockdown of these genes had the opposite results.…”
Section: Effect Of Arginase Expression On Arginine Metabolismsupporting
confidence: 72%
See 3 more Smart Citations